Bioorthogonal Non-Canonical Amino Acid Tagging (BONCAT) to detect newly synthesized proteins in cells and their secretome - Elizabeth P. Anim; Justin Mezzanotte; Siwei Chu; Ursula Stochaj (PLoS ONE, 2025)
Background Cells respond to physiological or pathological stimuli by altering the composition of the proteins they produce. This adaptation includes changes to newly translated polypeptides that are destined for intracellular compartments or secretion. The secretome is relevant to cell physiology, as it promotes autocrine, paracrine, and endocrine signaling. These events control cell death, tissue repair, and other regenerative processes. Uncovering the changes in de novo protein synthesis under different growth conditions requires reliable methods to identify and quantify newly synthesized proteins. Bioorthogonal Noncanonical Amino Acid Tagging (BONCAT) can generate this information with high spatiotemporal resolution. Methods We developed a BONCAT-based protocol to characterize proteins synthesized de novo in mammalian cells. Cultured HeLa cells are used as a model system, as their cell physiology is particularly well understood. The current protocol employs L-azidohomoalanine as an L-methionine analog, which is incorporated into newly translated polypeptide chains. After the incubation period, cells and the growth medium, which contains the secretome, are processed separately. Specifically, proteins are alkylated, and L-azidohomoalanine is modified with a biotin affinity tag. Proteins are collected using a rapid precipitation method, which is compatible with the subsequent affinity purification of biotinylated polypeptides. The affinity-purified material can be used for diverse downstream applications, such as Western blotting. Our experiments illustrate the feasibility of different steps of the protocol. Moreover, we discuss potential bottlenecks of the procedure and provide solutions that address these obstacles. Discussion Our work demonstrates the power of a modified BONCAT protocol to study newly produced proteins in growing cells and their secretome. This method will be useful to examine the proteome and secretome changes that are linked to the altered performance of cells, tissues, and organs during aging, disease, or other challenging conditions.